An exploratory factor analysis (EFA) in determining dimensions of school culture in morality of secondary school students South-Western Nigeria - Muhammed-Lawal, Adam Adesina; Abd Rashid, Adnan (Leena and Luna International, Chikusei, Japan., 2019)
Students do not develop in isolation because they need to mingle with their colleagues in order to develop physically, academically and morally; which will assist the students in all spheres of life. Few studies however have been conducted to empirically examine the underlining factors determining the influence of School culture on the morality of secondary school students in southwestern part of Nigeria. The primary objective of this study was to validate the major components of School culture by using explanatory factor analysis (EFA). The cross sectional research design was utilized to answer the research questions. A sample comprised 365 respondents was selected from the population of secondary school students in southwestern Nigeria to answer a self-developed questionnaire. The study validates the factors structure of School culture using SPSS version 24. From the Exploratory Factor Analysis (EFA), the findings from the study have successfully identified four factors with (52%) percentage of total variance explained.